Hubungan Pola Asuh Otoriter Dengan Perilaku Agresif Siswa SDN 74 Kota Bengkulu - Sari, Ratna (Jurnal PGSD, 2024)
This study aims to determine the relationship between authoritarian parenting with the aggressive behavior of students in grade V SDN 74 Kota Bengkulu. This type of research is quantitative research using correlational research method. The population in this study is all students in class V SDN 74 Kota Bengkulu which amounted to 96 people and all will be sampled in this study by using total sampling technique. Research instruments and data collection techniques used questionnaires. Data analysis techniques used the iproduct moment correlation formula and t test. The results of this study indicated that the value of rcount = 0.375 is greater than rtable = 0.202, with percent contribution = 14.06%, and tcount = 3.919. So it can be concluded that there is a positive significant relationship between authoritarian parenting with the aggressive behavior of students of grade V SDN 74 Kota Bengkulu.